2015
DOI: 10.1007/s11187-015-9652-2
|View full text |Cite
|
Sign up to set email alerts
|

Firm size and spillover effects from foreign direct investment: the case of Romania

Abstract: This paper introduces firm size in the analysis of the productivity spillovers of foreign direct investment. Our analysis of a panel of Romanian firms reveals two main findings: only medium-sized foreign firms generate spillovers, and domestic firms’ size is of limited importance to identify which firms absorb spillovers. To explain these findings, we show that large foreign firms are less embedded in the domestic economy because they are more likely to bring their own suppliers, import intermediate inputs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…In a panel of 4000 UK manufacturing firms covering the period 1991-1996, Girma et al (2001) showed that FDI spillovers benefit domestic firms with a relatively small technology gap relative to technology leaders. Similar evidence was found for Romanian (Lenaerts and Merlevede 2015) and Hungarian firms (Békés et al 2009).…”
Section: Inward Foreign Direct Investment and Productivitysupporting
confidence: 80%
“…In a panel of 4000 UK manufacturing firms covering the period 1991-1996, Girma et al (2001) showed that FDI spillovers benefit domestic firms with a relatively small technology gap relative to technology leaders. Similar evidence was found for Romanian (Lenaerts and Merlevede 2015) and Hungarian firms (Békés et al 2009).…”
Section: Inward Foreign Direct Investment and Productivitysupporting
confidence: 80%
“…In practice, we use information from two different input-output tables. Blalock &Gertler, 2008, andMerlevede, 2015), but it allows us to control for possible changes in the relationship between sectors over time. Similarly, backward technological spillovers at the industry level are a function of total R&D expenditures in the industries supplied by industry s at time t:…”
Section: Variables and Descriptive Statisticsmentioning
confidence: 99%
“…The age of the owner, foreign trade regulations, taxes, other regulations, political instability, inflation and lack of skilled labor adversely reduced the probability of a firm's growth in terms of employment opportunities. Olivera and Fortunato (2008) and Lenaerts and Merlevede (2015) claim that a firm's growth is mainly explained by the firm's age and size.…”
Section: Determinants Of Productivity Growth In Service Firmsmentioning
confidence: 99%